Evaluation of the direct and indirect impact on pneumonia hospitalization after almost a decade of the 10-valent pneumococcal non- typeable Haemophilus influenzae protein D conjugate vaccine in Brazil: Evaluation of 10-valent pneumococcal vaccine on pneumonia hospitalization in Brazil - Hammes Varela, Fernanda; Costa, Eduardo; Comerlato Scotta, Marcelo; Tetelbom Stein, Renato (Clinical and Biomedical Research, 2023)
Introduction: Pneumococcal pneumonia is a leading cause of severe disease, leading to approximately 2.2 million hospital admissions in 2019 in Brazil. Since 2010, the 10-valent pneumococcal non-typeable Haemophilus influenzae protein D conjugate vaccine was introduced in Brazil, as part of the National Immunization Program (NIP) with universal access, approximated coverage of 91.4% in 2019. Although studies from many countries are available, there is still a need to understand the effect of the vaccine introduction on the incidence of pneumonia hospitalizations in Brazil. Methods: Data on hospitalization associated with the diagnosis of pneumonia in the population assisted by the Brazilian Public Health System were accessed to fit a time series analysis, which tested the main hypothesis of the influence of vaccination on the trends for the incidence of pneumonia hospitalizations. Results: The post-vaccination period showed a negative trend, reducing 1.75, 0.16, and 0.11 cases per 100,000 inhabitants per month for the groups < 1, 1–4, and 5–9 years old, respectively. In individuals older than 20 years, the post-vaccination period has a positive trend, but not as great as compared trends before the vaccination period. These results indicate a protective herd effect in the older population, nine years after introducing the pneumococcal vaccine in the NIP. Conclusion: Vaccination with pneumococcal conjugated vaccine reduces hospitalizations associated with pneumonia diagnosis in vaccinated and non-vaccinated populations in a sustained and progressive manner.